2015
DOI: 10.1039/c5nr00399g
|View full text |Cite
|
Sign up to set email alerts
|

Non-exponential resistive switching in Ag2S memristors: a key to nanometer-scale non-volatile memory devices

Abstract: The dynamics of resistive switchings in nanometer-scale metallic junctions formed between an inert metallic tip and an Ag film covered by a thin Ag2S layer are investigated. Our thorough experimental analysis and numerical simulations revealed that the resistance change upon a switching bias voltage pulse exhibits a strongly non-exponential behaviour yielding markedly different response times at different bias levels. Our results demonstrate the merits of Ag2S nanojunctions as nanometer-scale non-volatile memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
5
28
0
Order By: Relevance
“…stable nanojunction while f drive was varied over five orders of magnitude. We found that R OFF /R ON linearly increases with while a logarithmic decrease is observed with increasing f drive , in agreement with the so-called "voltage-time dilemma" [22,35] enabling non-volatile data storage. Exemplary traces selected from the parameter regimes highlighted in white in Figure 2a demonstrate these tendencies, as illustrated in Figure 2b and Figure 2c, where either or f drive was stepped while the other parameter was kept constant.…”
Section: Structural and Electrical Characterizationsupporting
confidence: 82%
See 3 more Smart Citations
“…stable nanojunction while f drive was varied over five orders of magnitude. We found that R OFF /R ON linearly increases with while a logarithmic decrease is observed with increasing f drive , in agreement with the so-called "voltage-time dilemma" [22,35] enabling non-volatile data storage. Exemplary traces selected from the parameter regimes highlighted in white in Figure 2a demonstrate these tendencies, as illustrated in Figure 2b and Figure 2c, where either or f drive was stepped while the other parameter was kept constant.…”
Section: Structural and Electrical Characterizationsupporting
confidence: 82%
“…They were directly followed by the onset of stable hysteretic traces without the need of any further dedicated electroforming procedure. We argue, that the indention of the tip to the surface layer reduces the effective thickness of the dielectric layer resulting in the down-scaling of the electroforming voltage to the range of the set voltage in agreement with the tendency commonly observed in nanoscale resistive switching systems [8,9,22]. Resistive switching was characterized by the analysis of hysteretic I(V) traces that were acquired by using the setup shown in the upper inset of Figure 1a.…”
Section: Structural and Electrical Characterizationsupporting
confidence: 81%
See 2 more Smart Citations
“…20 Application of nanostructured silver sulde holds much promise in microelectronics, where Ag 2 S/Ag heteronanostructures and nanocomposites are used in nonvolatile memory devices and resistive switches. [21][22][23] Their action is based on the phase transition of acanthite a-Ag 2 S into argentite b-Ag 2 S. [12][13][14][23][24][25][26][27][28] According to the phase diagram of the Ag-S system, 29 silver sulde Ag 2 S has three polymorphic modications. The lowtemperature semiconductor phase a-Ag 2 S (acanthite) with a monoclinic crystal structure exists at temperatures below $450 K. b-Ag 2 S (argentite) phase has a body-centered cubic (bcc) lattice, exists in the temperature range 452-859 K, and possesses superionic conductivity.…”
Section: Introductionmentioning
confidence: 99%